Authentication of Polygonati Odorati Rhizoma and other two Chinese Materia Medica of the Liliaceae family by pharmacognosy technique with GC–MS analysis. Issue 2 (19th November 2014) - Liu, Yingjiao; Liu, Canhuang; Yu, Yafei; Xu, Bei; Gong, Limin; Zeng, Xiaoyan; Xiao, Lan; Cheng, Qilai; Liu, Tasi
ABSTRACT Yuzhu (Polygonati Odorati Rhizoma), Kangdingyuzhu (Polygonati Prattii Rhizoma), and zhugenqiyuzhu (Disporopsis Fuscopictae Rhizoma) are of the same family, but of different genera. They have all often used in Chinese Materia Medica (CMM) as Polygonati Odorati Rhizoma in China market. Three species of CMM are confused. For better application, we need to identify these plants accurately. This study use pharmacognosy technique and GC‐MS analysis, three species of CMM were authenticated. In macroscopic characteristics, the fruit of Polygonati Odorati Rhizoma is blue‐black, while the other two are maroon and dark purple orderly. Nodes of Polygonati Odorati Rhizoma are upward and light uplift, about 1 cm spacing, while the other are not. As for microscopic characteristics, the cortex of Polygonati Odorati Rhizoma only occupies about 1/5 of the radius of the transverse section with inconspicuous endodermis, which is much smaller than others. The type of vascular bundles of Polygonati Odorati Rhizoma is closed collateral, but the other is amphivasal. Raphides of calcium oxalate are scattered, but Raphides of the other two are like brooms and neat rows. GC–MS analysis of essential oil could provide different characteristics to distinguish three species. Twenty‐three compounds were identified from essential oil of Polygonati Odorati Rhizoma and the main components were n‐hexadecanoic acid (49.45%), while n‐hexadecanoic acid of the other two are 23.92% and 9.45%. The content of n‐hexadecanoic is strongly different. This research was aimed to establish a method by pharmacognosy and GC–MS analysis to identify three CMM and for providing scientifical data to ensure accuracy of origin of three species. Microsc. Res. Tech. 78:119–127, 2015. © 2014 Wiley Periodicals, Inc.